Loss of functional connectivity is an early imaging marker in primary lateral sclerosis. Issue 7 (2nd October 2018) - Clark, Michael G.; Smallwood Shoukry, Rachel; Huang, Caleb J.; Danielian, Laura E.; Bageac, Devin; Floeter, Mary Kay
Abstract: Objective: The clinical diagnosis of primary lateral sclerosis can only be made after upper motor neuron symptoms have progressed for several years without developing lower motor neuron signs. The goal of the study was to identify neuroimaging changes that occur early in primary lateral sclerosis, prior to clinical diagnosis. Methods: MRI scans were obtained on 13 patients with adult-onset progressive spasticity for five years or less who were followed longitudinally to confirm a clinical diagnosis of primary lateral sclerosis. Resting state functional MRI, diffusion tensor imaging, and anatomical images were obtained. These "pre-PLS" patients were compared to 18 patients with longstanding, established primary lateral sclerosis and 28 controls. Results: Pre-PLS patients had a marked reduction in seed-based resting-state motor network connectivity compared to the controls and patients with longstanding disease. White matter regions with reduced fractional anisotropy were similar in the two patient groups compared to the controls. Patients with longstanding disease had cortical thinning of the precentral gyrus. A slight thinning of the right precentral gyrus was detected in initial pre-PLS patients' scans. Follow-up scans in eight pre-PLS patients 1–2 years later showed increasing motor connectivity, thinning of the precentral gyrus, and no change in diffusion measures of the corticospinal tract or callosal motor region. Conclusions: Loss of motor functional connectivity is an early imaging marker in primary lateral sclerosis. This differs from literature descriptions of amyotrophic lateral sclerosis, warranting further studies to test whether resting-state functional MRI can differentiate between amyotrophic lateral sclerosis and primary lateral sclerosis at early disease stages.